2020
DOI: 10.1101/2020.12.18.423538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Body size affects immune cell proportions in birds and non-volant mammals, but not bats

Abstract: Powered flight has evolved several times in vertebrates and constrains morphology and physiology in ways that likely have shaped how organisms cope with infections. Some of these constraints likely have impacts on aspects of immunology, such that larger fliers might prioritize risk reduction and safety. Addressing how the evolution of flight may have driven relationships between body size and immunity could be particularly informative for understanding the propensity of some taxa to harbor many virulent and so… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…In addition, the difference in the immune defense capability of hosts with varying BCIs may not be consistently correlated or sufficient in itself to account for differences in the observed parasite abundance [ 57 ]. For instance, in bats lymphocyte and neutrophil proportions are generally similar irrespective of their body mass [ 58 ], which may explain why bats with lower BCI may not be more vulnerable to parasites than those in better condition [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the difference in the immune defense capability of hosts with varying BCIs may not be consistently correlated or sufficient in itself to account for differences in the observed parasite abundance [ 57 ]. For instance, in bats lymphocyte and neutrophil proportions are generally similar irrespective of their body mass [ 58 ], which may explain why bats with lower BCI may not be more vulnerable to parasites than those in better condition [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The absolute number of each white blood cell type was then determined by multiplying its relative abundance by the estimated TWBC count (Becker et al 2021a). A subset of the hematology data from 2017 and 2018 were published previously (Becker et al 2021a;Cornelius Ruhs et al 2021).…”
Section: White Blood Cell Counts and Statistical Analysesmentioning
confidence: 99%
“…Evidence of increased investment in at least some types of immunity in larger animals is also beginning to emerge. An investigation of the association of immune cell concentrations with body mass in over 250 mammalian species found that neutrophils, part of the innate immune system, scaled hypermetrically (concentrations were positively associated with body mass) whereas lymphocytes, which participate in both the innate and adaptive immune systems, scaled nearly isometrically (concentrations were slightly negatively associated with body mass) (Downs, Dochtermann, et al, 2020;Ruhs, Becker, et al, 2020; see also Ruhs, Martin, et al, 2020). A study examining the antibacterial activity in serum against three bacterial species -Escherichia coli, Salmonella enterica, and Micrococcus luteus -in over 160 terrestrial mammals found that antibacterial activity scaled isometrically with body size, which is more than would be predicted by the hypometric scaling of metabolic rates (Downs, Schoenle, et al, 2020).…”
Section: Body Size and Longevity In Homo And Its Impact On Immune Investmentmentioning
confidence: 99%